(untitled) (Journal of Bio-Science, 2014)
Context: Local farmers believe that the seasonal ponds and ditches which can retain water for 4 to 6 months in a year cannot be utilized for fish production but in fact such waters hold tremendous potential for culture of small indigenous fish species. Objectives: To evaluate the effects of fertilization and feeding in the growth and production of Puntius sophore culture in seasonal ponds. Materials and Methods: Six ponds were used during this study under two treatments. Two treatments such as T1 (only fertilizer) and T2 (fertilization and supplementary feeding) were run in triplicate. P. sophore was stocked in the two treatments at the rate of 15500 ha-1 after necessary pond preparation and fertilization. Results: Important physico-chemical factors viz., temperature, transparency, pH dissolved oxygen and total hardness of two treatments were found within the productive ranges. Four groups of phytoplankton were found in the ponds namely Bacillariophyceae, Chlorophyceae, Cyanophyceae and Euglenophyceae and two groups of zooplankton viz. Crustacea and Rotifera. P. sophore successfully breed in both treatments. However, the number of fish harvested was 122135 ha-1 in T1 and 113335 ha-1 in T2. Yet the total production was higher in T2 (1091.40 kg ha-1) than in T1 (842.72 kg ha-1) as the individuals found in T2 gained more weight than those in T1 reflecting the effects of regular feeding. Conclusion: The study indicated that both fertilizer and feed based treatment was to improve more production than only fertilizer based treatment under seasonal pond conditions. DOI: http://dx.doi.org/10.3329/jbs.v20i0.17735 J. bio-sci. 20: 135-142, 2012